The Effect of Spin-Off Policy on Financing Growth in Indonesian Islamic Banking Industry - Mohammad Al Arif (Al-Ulum, 2015)
The purpose of this paper is to analyze the relationship between spin-off policy on the financing growth of Islamic banking industry in Indonesia. This research used panel regression with fixed effect. The variable used in this paper is dummy variabel of spin-off, and also included the internal factor of industry such as third party fund, and efficiency ratio (measured by BOPO). Besides the internal factor, this research also included the external factor such as inflation rate, economic growth rate, and interest rate from conventional banking. The result shows that only third part funds and interest rate had an impact on the financing growth in spin-off banks. The spin-off policy doesn’t have an impact on the financing growth in spin-off banks